Food Safety Management in China : What China can Lean from Canada? - WU, Yiming (Advances in Social Sciences Research Journal, 2016)
Food safety has become an issue of public policy because it has much to do with people’s vital interests. The growing unrest over food safety in China reached a climax in early 2007.Years after the melamine-in-milk scandal that made 300,000 children sick, and after China passed its first-ever food safety law in response in 2009, the country is still struggling to keep its food supply healthy. It is well known that Canada's food safety system is ranked the best in the world. Managing food safety risks in Canada is the shared responsibility of governments, food industries (including producers, processors, retailers, and food service establishments), and consumers. This paper addresses research that aims to make a comparative study of food safety management in China and Canada, from the perspective of the functions and responsibilities of each administrative department and the rights, power and liabilities among different stakeholders. The outcome of the study is to compare and contrast the Canadian system with China and to propose a complete system of food safety management in China.